Analysis of the Partnership Between Turnip Farmers and PT VAI Company in Purba District - Roeskani Sinaga; Wahyunita Sitinjak; Jhon Kariando Purba (Jurnal Penelitian Pendidikan IPA, 2025)
This study aims to analyze the form of partnership implementation between turnip farmers and PT VAI, examine the benefits of this form of partnership for turnip farmers, and analyze turnip farming income. This study was conducted in Purba District, Simalungun Regency. Farmers in Nagori Pamatang Purba were designated as sample villages from the population that became research respondents. The sampling technique and population in this study used Purposive Sampling and Snowball techniques. The data analysis method used descriptive analysis of PT VAI's contract with partner farmers, farm income analysis, and R/C Ratio. The results of the study indicate that the form of partnership between PT VAI and turnip farmers in Purba District is a subcontract form. Where farmers and PT VAI have a contract regarding seeds, production prices and product quality. The benefits that are definitely obtained by farmers as partners include being able to help in procuring seeds. Farmers get convenience for seeds because they do not have to do their own seeding, thereby reducing the risk of failure because the seeds are ready to plant. The benefits of marketing guarantees provide a guarantee that the resulting product will be immediately sellable. One hundred percent of turnip farmer respondents answered that they received benefits in marketing convenience. This aligns with the initial rationale and hope for joining, which is that farmers won't have to search for markets to sell their products. Marketing guarantees can also motivate farmers to produce according to PT VAI's criteria so their products are accepted. Radish farming in Pematang Purba Village generates substantial income and is considered viable, as the R/C ratio analysis shows a value of 3.01, meaning that for every Rp 1.00 spent, a return of Rp 3.01 is generated.